New agendas in remote sensing and landscape archaeology in the Near East : studies in honour of Tony J. Wilkinson - Lawrence, Dan; Altaweel, Mark; Philip, Graham (2020)
This volume presents papers in honour of Tony James Wilkinson, who was Professor of Archaeology at Durham University from 2006 until his death in 2014. Though commemorative in concept, the volume is an assemblage of new research representing emerging agendas and innovative methods in remote sensing and their application in Near Eastern archaeology.